2013
DOI: 10.1164/rccm.201303-0442oc
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 7 Rapidly Relaxes Human Airways

Abstract: Rationale: Toll-like receptors (TLRs) 7 and 8 detect respiratory virus single-stranded RNA and trigger an innate immune response. We recently described rapid TLR7-mediated bronchodilation in guinea pigs. Objectives: To characterize TLR7 expression and TLR7-induced airway relaxation in humans and in eosinophilic airway inflammation in guinea pigs. To evaluate the relaxant effects of other TLRs. Methods: Human airway smooth muscle strips were contracted with methacholine in vitro, and responses to TLR7 and TLR8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 48 publications
1
38
2
3
Order By: Relevance
“…Their recently reported ability to rapidly relax airways (11,22) has increased their interest in the treatment of pulmonary disease. The present study verified the ability for imiquimod to induce a strong and rapid dilatory effect in isolated guinea pig airways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their recently reported ability to rapidly relax airways (11,22) has increased their interest in the treatment of pulmonary disease. The present study verified the ability for imiquimod to induce a strong and rapid dilatory effect in isolated guinea pig airways.…”
Section: Discussionmentioning
confidence: 99%
“…Using our in vitro and in vivo models, we next examined molecules and associated signaling pathways involved in bronchodilation, including the role of NO and prostanoids, previously implicated in imiquimod-mediated bronchodilation (11,22), CO, cGMP, PKG, and PKA.…”
Section: Imiquimod Relaxes Precontracted Guinea Pig Airways In Vitro mentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were published in the Journal in 2013 that identified new factors that may affect airway smooth muscle contraction and relaxation (55)(56)(57). Two of the studies applied multiple modalities to mouse, guinea pig, and human tissues and identified transmembrane protein 16A, a calcium-activated chloride channel, and Toll-like receptor 7, respectively, as factors that modify the response of airway smooth muscle to contractile agents (56,57).…”
Section: Pathways That Affect Smooth Musclementioning
confidence: 99%
“…Two of the studies applied multiple modalities to mouse, guinea pig, and human tissues and identified transmembrane protein 16A, a calcium-activated chloride channel, and Toll-like receptor 7, respectively, as factors that modify the response of airway smooth muscle to contractile agents (56,57). The third study combined laser capture microdissection of human airway biopsies and RNA sequencing to identify two genes (FAM129A and SYNPO2) that were significantly changed in expression with corticosteroids in asthma and which correlated with degree of airway hyper-responsiveness (55).…”
Section: Pathways That Affect Smooth Musclementioning
confidence: 99%